A Review Paper on Cuckoo Search Algorithm (CSA) (International Journal of Innovative Research in Computer Science & Technology, 2022)
CS was first proposed by Xin-She Yang  and Suash Deb in 2009, and it has received a lot of interest  because of its potential efficiency in handling a variety of  optimisation issues and contributes substantial. Because of  the publication of a large number of studies in the previous  several years about cuckoo search, the body here you will find a summary of the majority of the research on cuckoo  search that has been published in peer-reviewed  publications a thorough classification of these references  into relevant categories might provide a basis for  subsequent study. Many studies on cuckoo search have  been published in recent years, and the field on the subject  has grown substantially. EAs' main purpose is to find the  internationally optimum or near-optimal solutions in the  lowest amount of time. This section summarizes the  majority of the particle swarm optimization investigations  that have been published in consensus journals and at  conventions so far. These resources may be organized into  appropriate sections and used as a jumping off location for  further research.
Keywords: Cuckoo Algorithm; Engineering optimization; Hybrid; Search; Variant